Battery power supply and DC to AC inverter / Erwan Turiman and Ismail Ahmad - Turiman, Erwan; Ahmad, Ismail (2005)
This project is valuable and acceptable for a daily use and also for an emergency case like blackout. This project is called power supply (source-part). It required some common electric and electronic devise, such as transformer inverter, transistor, capacitor, resister etc. Our project is suitable to use for any electrical devise. This is because our supply comes from a car battery. The input supply is 12V dc and our output is +230V ac. We use the dc to ac inverter circuit to convert the voltage supply from input dc to output ac. From our part the output will be input to our member’s part. There are many benefit can we get from this power supply because we just take a car battery for their source. A car battery are easy to find and it also suitable to use. It will make our life even easier.